An Exploration of Novel Bioactives from the Venomous Marine Annelid Glycera alba - Sónia Campos; Ana P. Rodrigo; Inês Moutinho Cabral; Vera M. Mendes; Bruno Manadas; Mariaelena D’Ambrosio; Pedro M. Costa (Toxins, 2023)
The immense biodiversity of marine invertebrates makes them high-value targets for the prospecting of novel bioactives. The present study investigated proteinaceous toxins secreted by the skin and proboscis of Glycera alba (Annelida: Polychaeta), whose congenerics G. tridactyla and G. dibranchiata are known to be venomous. Proteomics and bioinformatics enabled the detection of bioactive proteins that hold potential for biotechnological applications, including toxins like glycerotoxins (GLTx), which can interfere with neuromuscular calcium channels and therefore have value for the development of painkillers, for instance. We also identified proteins involved in the biosynthesis of toxins. Other proteins of interest include venom and toxin-related bioactives like cysteine-rich venom proteins, many of which are known to interfere with the nervous system. Ex vivo toxicity assays with mussel gills exposed to fractionated protein extracts from the skin and proboscis revealed that fractions potentially containing higher-molecular-mass venom proteins can exert negative effects on invertebrate prey. Histopathology, DNA damage and caspase-3 activity suggest significant cytotoxic effects that can be coadjuvated by permeabilizing enzymes such as venom metalloproteinases M12B. Altogether, these encouraging findings show that venomous annelids are important sources of novel bioactives, albeit illustrating the challenges of surveying organisms whose genomes and metabolisms are poorly understood.